Distinct Regulation of Host Responses by ERK and JNK MAP Kinases in Swine Macrophages Infected with Pandemic (H1N1) 2009 Influenza Virus - Gao, Wei; Sun, Wenkui; Qu, Bingqian; Cardona, Carol J.; Powell, Kira; Wegner, Marta; Shi, Yi; Xing, Zheng (PLOS ONE, 2012)
Swine influenza is an acute respiratory disease in pigs caused by swine influenza virus (SIV). Highly virulent SIV strains cause mortality of up to 10%. Importantly, pigs have long been considered “mixing vessels” that generate novel influenza viruses with pandemic potential, a constant threat to public health. Since its emergence in 2009 and subsequent pandemic spread, the pandemic (H1N1) 2009 (H1N1pdm) has been detected in pig farms, creating the risk of generating new reassortants and their possible infection of humans. Pathogenesis in SIV or H1N1pdm-infected pigs remains poorly characterized. Proinflammatory and antiviral cytokine responses are considered correlated with the intensity of clinical signs, and swine macrophages are found to be indispensible in effective clearance of SIV from pig lungs. In this study, we report a unique pattern of cytokine responses in swine macrophages infected with H1N1pdm. The roles of mitogen-activated protein (MAP) kinases in the regulation of the host responses were examined. We found that proinflammatory cytokines IL-6, IL-8, IL-10, and TNF-α were significantly induced and their induction was ERK1/2-dependent. IFN-β and IFN-inducible antiviral Mx and 2′5′-OAS were sharply induced, but the inductions were effectively abolished when ERK1/2 was inhibited. Induction of CCL5 (RANTES) was completely inhibited by inhibitors of ERK1/2 and JNK1/2, which appeared also to regulate FasL and TNF-α, critical for apoptosis in pig macrophages. We found that NFκB was activated in H1N1pdm-infected cells, but the activation was suppressed when ERK1/2 was inhibited, indicating there is cross-talk between MAP kinase and NFκB responses in pig macrophages. Our data suggest that MAP kinase may activate NFκB through the induction of RIG-1, which leads to the induction of IFN-β in swine macrophages. Understanding host responses and their underlying mechanisms may help identify venues for effective control of SIV and assist in prevention of future influenza pandemics.